Efficacy and safety of a basal insulin + 2‐3 oral antihyperglycaemic drugs regimen versus a twice‐daily premixed insulin + metformin regimen after short‐term intensive insulin therapy in individuals with type 2 diabetes: The multicentre, open‐label, randomized controlled BEYOND‐V trial. Issue 10 (28th June 2022) - Pan, Qi; Li, Yijun; Wan, Hailong; Wang, Junfen; Xu, Binhua; Wang, Guoping; Jiang, Chengxia; Liang, Li; Feng, Wei; Liu, Jingcheng; Wang, Ting; Zhang, Xia; et al.
Abstract: Aim: To compare the efficacy and safety of basal insulin glargine 100 units/ml (Gla) + 2‐3 oral antihyperglycaemic drugs (OADs) with twice‐daily premixed insulin aspart 70/30 (Asp30) + metformin (MET) after short‐term intensive insulin therapy in adults with type 2 diabetes in China. Materials and Methods: This open‐label trial enrolled insulin‐naïve adults with type 2 diabetes and an HbA1c of 7.5%‐11.0% (58‐97 mmol/mol) despite treatment with 2‐3 OADs. All participants stopped previous OADs except MET, then received short‐term intensive insulin therapy during the run‐in period, when those with a fasting plasma glucose of less than 7.0 mmol/L and 2‐hour postprandial glucose of less than 10.0 mmol/L were randomized to Gla + MET + a dipeptidyl peptidase‐4 inhibitor or twice‐daily Asp30 + MET. If HbA1c was more than 7.0% (>53 mmol/mol) at week 12, participants in the Gla group were added repaglinide or acarbose, at the physician's discretion, and participants in the Asp30 group continued to titrate insulin dose. The change in HbA1c from baseline to week 24 was assessed in the per protocol (PP) population (primary endpoint). Results: There were 384 enrollees (192 each to Gla and Asp30); 367 were included in the PP analysis. The threshold for non‐inferiority of Gla + OADs versus Asp30 + MET was met, with a least squares mean change from baseline in HbA1c of –1.72% and –1.70% (–42.2 and –42.1 mmol/mol), respectively (estimated difference –0.01%; 95% CI –0.20%, 0.17% [–0.1 mmol/mol; 95% CI –2.2, 1.9]). Achievement of HbA1c less than 7.0% (<53 mmol/mol) was comparable between the groups (60% vs. 57%). The proportion of participants with any (24% vs. 38%; P =  .003), symptomatic (19% vs. 31%; P  = .007) or confirmed hypoglycaemia (18% vs. 33%; P <  .001) was lower in the Gla + OADs group. Conclusions: Compared with Asp30 + MET, Gla + 2‐3 OADs showed similar efficacy but a lower hypoglycaemia risk in Chinese individuals with type 2 diabetes who had undergone short‐term intensive insulin therapy.